2022
DOI: 10.1002/ppul.26253
|View full text |Cite|
|
Sign up to set email alerts
|

Refinement of newborn screening for cystic fibrosis with next generation sequencing

Abstract: Background Newborn screening for cystic fibrosis (CF) has been underway universally in the United States for more than a decade, as well in most European countries, and algorithms have been evolving throughout this period with quality improvement projects as immunoreactive trypsinogen (IRT) determinations alone have been transformed to a 2‐tier strategy with DNA analyses. Objective To apply next generation sequencing (NGS) as a screening method to expand the DNA tier and identify substantially more variants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The decrease in CRMS/CFSPID cases was accompanied by a decrease in sensitivity and positive predictive value of the programme 15 . A study from Wisconsin showed that when the NBS algorithm included CFTR variants with varying clinical consequences (VVCCs), the ratio of CRMS/CFSPID to CF cases was 1.4:1 16 . After excluding VVCCs, except for R117H, the analysis indicated a decrease in the number of patients with two variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in CRMS/CFSPID cases was accompanied by a decrease in sensitivity and positive predictive value of the programme 15 . A study from Wisconsin showed that when the NBS algorithm included CFTR variants with varying clinical consequences (VVCCs), the ratio of CRMS/CFSPID to CF cases was 1.4:1 16 . After excluding VVCCs, except for R117H, the analysis indicated a decrease in the number of patients with two variants.…”
Section: Resultsmentioning
confidence: 99%
“…15 A study from Wisconsin showed that when the NBS algorithm included CFTR variants with varying clinical consequences (VVCCs), the ratio of CRMS/CFSPID to CF cases was 1.4:1. 16 After excluding VVCCs, except for R117H, the analysis indicated a decrease in the number of patients with two variants. Specifically, of the 18 infants diagnosed with CF, only 17 (94%) had two pathogenic variants.…”
Section: The Frequency Of Crms/cfspid After Nbs For Cfmentioning
confidence: 97%
“…The CF NBS algorithms used in the United States 14 are quite variable, particularly the IRT cutoff values employed and a number of variants in CFTR panels, but as knowledge and technologies have increased, 16–18 better tests have emerged 3 . Once a region like New Jersey begins with a screening protocol, however, it is difficult to change as other screening methods evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF), a common, life‐shortening, autosomal recessive genetic disorder caused by pathogenic variants in the cystic fibrosis transmembrane conductance regulator ( CFTR ) that can be detected through newborn screening (NBS). All CF NBS methods begin with the biomarker immunoreactive trypsinogen (IRT) 1–3 . Although IRT followed by a second IRT to confirm hypertrypsinogenemia was the original screening test applied to dried blood spot specimens, 4,5 this method was supplanted in 1993 when Gregg et al 5 reported the IRT/DNA(F508del) algorithm that resolved the problems with IRT described by Rock et al 6 After Farrell et al 7 reported significant nutritional benefits of early diagnosis through NBS, as established in a randomized clinical trial, New Jersey implemented CF NBS in 2001 with IRT/DNA (F508del), the standard method of that time 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation